Social Return On Investment (SROI) Program for Empowering Pepper Farmers in Petaling Banjar Village - yosanovia novia; Jamilullah Jamilullah; , Elis Trisnawati; Euis Intan Anovani; Khidayatul Munawwaroh; Firdaus Firdaus (Community Development Journal, 2021)
Pepper farmers in Petaling Banjar Village, Mendo Barat District, Bangka Regency, Bangka Belitung Islands Province who are members of the Pepper Farmer Empowerment Program are a community group assisted by PT RBT's CSR. As a social investment, the implementation of CSR activities in the long term will bring business returns in the form of profits for the company. Social Return on Investment (SROI) is a method used to measure the social impact of CSR activities that does not only calculate the value of profits in the form of money, but includes a broader concept that includes social, economic, and environmental values. This study involved a number of respondents who were representatives of key stakeholders, namely: 10 pepper farmers, 6 general public, 1 community leader and 2 people from the Petaling Banjar village government. Data were collected using in-depth interview techniques, Focus Group Discussion (FGD), field observations, and the use of secondary data from PT RBT's CSR program documentation. The results showed that the overall SROI value obtained was 1.76. This means that every IDR 1 invested has a benefit of IDR 1.76 when the SROI measurement is carried out. When viewed from a social and economic perspective, the Petaling Banjar Pepper Farmers Empowerment program can be said to be feasible and successful